Ateroprotective effects of Plinia cauliflora in. New Zealand rabbits: beyond the lipid-lowering effect - Cestari, Ana Paula; Gasparotto, Francielly Mourão; Kassuya, Cândida Aparecida Leite; Lacerda, Tauany Milan Ribeiro; Donadel, Guilherme; Moura, Catia Sari; Ceranto, Daniela Boleta; Jacomassi, Ezilda; Alberton, Odair; Tramontini, Salviano Belletini; Bertoncello, Luana Ale; Gasparotto Junior, Arquimedes; et al. (Frontiers in Pharmacology, 2024)
Plinia cauliflora [Mart.] Kausel (Myrtaceae), popularly known as "jabuticaba," is a fruit species native to Brazil. Despite extensive widespread usage, its antiatherosclerotic properties' impact remains unknown. Thus, the present study aimed to investigate the cardioprotective effects of a preparation obtained from the fruit peels of P. cauliflora (EEPC). Male New Zealand rabbits received a 1% cholesterol-supplemented diet for 60 days. On the thirtieth day, the animals were divided into five experimental groups and received, once a day, by the oral route, the EEPC (10, 30, and 100 mg/kg), simvastatin (2.5 mg/kg), or vehicle for 30 days. At the end of the experimental period, peripheral blood and arterial branch samples were collected. The levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglyceride (TG), malondialdehyde (MDA), nitrotyrosine (NT), nitrite, interleukin 1 beta (IL-1b), interleukin 6 (IL-6), soluble inter-cellular adhesion molecule-1 (sICAM-1), and soluble vascular cell adhesion molecule-1 (sVCAM-1) levels were measured. Moreover, the catalase and superoxide dismutase levels were measured on the arterial samples. Histopathological analysis and arterial morphometry were also performed. The oral administration of ESEG significantly lowered the levels of lipids in rabbits that were fed a CRD diet. This treatment also adjusted the protective system against oxidation in the arteries by decreasing the oxidation of lipids and proteins. Additionally, the levels of IL-1b, IL-6, sICAM-1, and sVCAM-1 in the bloodstream decreased significantly, and this was accompanied by a reduction of atherosclerotic lesions in all branches of the arteries. The findings suggest that EEPC may be a possible option for additional management of atherosclerosis.